Favorable Pregnancy Outcomes in Women With Well-Controlled Pulmonary Arterial Hypertension - Corbach, Nadine; Berlier, Charlotte; Lichtblau, Mona; Schwarz, Esther I.; Gautschi, Fiorenza; Groth, Alexandra; Schüpbach, Rolf; Krähenmann, Franziska; Saxer, Stéphanie; Ulrich, Silvia (Frontiers in Medicine, 2021)
Introduction: Since pregnancy in women with pulmonary arterial hypertension (PAH) is associated with a high risk of morbidity and mortality, it is recommended that pregnancy should be avoided in PAH. However, some women with mild PAH may consider this recommendation as unsuitable. Unfortunately knowledge on pregnancy outcomes and best management of PAH during pregnancy is limited. Methods: Data from all women with PAH who were followed during pregnancy by a multidisciplinary team at a tertiary referral center for PAH and who delivered between 2004 and 2020 were retrospectively analyzed in a case series. PAH risk factor profiles including New York Heart Association (NYHA) functional class, NT-pro-BNP, echocardiographic pulmonary arterial pressure (PAP) and right heart function were analyzed prior to, during and following pregnancy. Results: In seven pregnancies of five women with PAH (median age 29 (27; 31) years), there were no abortions or terminations. Five pregnancies were planned (all in NYHA I-II), two incidental (NYHA II, III). During pregnancy none of the women had complications or clinical worsening of PAH. After a median pregnancy duration of 37 1/7 weeks all gave birth to healthy babies by cesarean section in spinal anesthesia. During pregnancy, PAP tended to increase, whilst the course of NYHA class and NT-pro-BNP were variable and no trend could be detected. Conclusion: Women with PAH with a low risk profile closely followed by a multidisciplinary team had a favorable course during and after pregnancy, resulting in successful deliveries of healthy newborns.